Modern family. The complete eighth season [videorecording (DVD)] - Koch, Chris (Director); Case, Ryan; O'Neill, Ed, 1946-; Vergara, Sofía, 1972-; Bowen, Julie (Twentieth Century Fox Home Entertainment, 2017)
Three non-traditional families face everyday challenges.